2021
DOI: 10.1101/2021.03.02.21252448
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dramatic Rise of Seroprevalence Rates of SARS-CoV-2 Antibodies among Healthy Blood Donors: The evolution of a Pandemic

Abstract: Background: The coronavirus disease 2019 (COVID-19) pandemic has resulted in more than 106 million cases of confirmed infection and more than 2.3 million deaths worldwide as of February 11th 2021. Seroprevalence studies are extremely useful in studying and assessing the epidemiological status in the community and the degree of spread. They help decision makers in implementing or relaxing mitigating measures to contain the disease in addition to other benefits. Objective: To study the seroprevalence rates of S… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 46 publications
(88 reference statements)
0
11
0
Order By: Relevance
“…Nevertheless, unfortunately, some of them have shown an increase in the seroprevalence of different populations. For example, a recent study in Jordan ( Sughayer et al, 2021 ) stated the importance of seroprevalence studies for SARS-CoV-2 infection among healthy blood donors. In this sense, we would like to complement by discussing some seroprevalence data in South America, a region that, as is known, has also been strongly affected by the coronavirus disease 2019 (COVID-19).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, unfortunately, some of them have shown an increase in the seroprevalence of different populations. For example, a recent study in Jordan ( Sughayer et al, 2021 ) stated the importance of seroprevalence studies for SARS-CoV-2 infection among healthy blood donors. In this sense, we would like to complement by discussing some seroprevalence data in South America, a region that, as is known, has also been strongly affected by the coronavirus disease 2019 (COVID-19).…”
Section: Introductionmentioning
confidence: 99%
“…2021, who found that there are 8 cases for every confirmed case by testing SARS-CoV-2 antibodies in 1374 blood donor. [50] This indicates that the official number of infections is lower than the real numbers according to the current representative sample. This behavior is concerning in two aspects.…”
Section: Discussionmentioning
confidence: 86%
“…Among the participants, 889 (87.6%) of them were residents of Joinville, with the rest of the donors from calculate the absolute risks of infection and predict the rate of viral spread [7,8]. In this context, it can be said that asymptomatic and pre-symptomatic infections contribute to herd immunity, and can boost up to 50% in the strength of infection at the peaks of an outbreak, making tracking of this population substantially important [9].…”
Section: Resultsmentioning
confidence: 99%